Co-exposure to ozone and polystyrene nanoplastic exacerbates cognitive impairment and anxiety-like behavior by regulating neuronal pyroptosis in mice - Anqi Dai; Xudong Liu; Yinuo Chen; Yougang Wang; Haomin Qi; Yan Zeng; Jinquan Li (Environment International)
Ozone (O3) and nanoplastics (NPs) are pervasive environmental pollutants that frequently co-occur in our heavily industrialized era. While it has been documented that exposure to O3 or NPs individually has neurotoxic effects, studies investigating their combined impact and the hazardous mechanisms resulting from co-exposure are limited. In this study, we established a mouse model co-exposure to polystyrene nanoparticles (PS-NPs) and O3, focusing on the prefrontal cortex (PFC), a brain region crucial for cognition and emotion. We examined the effects of O3 and PS-NPs on behavioral changes related to learning, memory, and anxiety, employing transcriptome sequencing alongside molecular and histopathological methods. Our findings indicate that combined exposure to O3 and PS-NPs disrupts the integrity of the blood–brain barrier, reducing Claudin 5 expression and leading to increased accumulation of PS-NPs in the PFC. Transcriptome sequencing demonstrated the involvement of the p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway and oxidative stress in the pathological changes observed in the PFC. Through immunohistochemical and immunofluorescence analysis, we observed enhanced microglial activation, which correlates with increased production of inflammatory factors. Additionally, western blot and immunofluorescence co-labeling analyses revealed elevated expression levels of GSDMD-N, caspase-1, IL-1β, and IL-18 proteins, which are associated with neuronal pyroptosis. Finally, immunofluorescence co-labeling confirmed that the activation of the p38 MAPK pathway in neurons is involved in co-exposure-induced pyroptosis. Meanwhile, N-Acetylcysteine (NAC), a common antioxidant, can alleviate neuroinflammation and neuronal pyroptosis in the PFC, and it rescued the cognitive deficits and anxiety-like behaviors observed in the co-exposed mice. Our study illustrates that co-exposure to O3 and NPs can aggravate damage to the blood–brain barrier and elevate oxidative stress levels in the PFC, thereby increasing the occurrence of neuroinflammation and may mediate neuronal pyroptosis through activation of the p38 MAPK pathway, ultimately contributing to neurobehavioral toxicity.